1995
DOI: 10.1111/j.1600-0749.1995.tb00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Melanins and Melanosomes Produced by Various Coat Color Mutants

Abstract: Pigmentation in the skin, hair, and eyes of animals is influenced by a number of genes that modulate the activity of melanocytes, the intervention of enzymatic controls at different stages of the melanogenic process, and the physico-chemical properties of the final pigment. The results of combined phenotypic, ultrastructural, biochemical, and chemical analyses of hairs of a variety of defined genotypes on a common genetic background performed in this study are consistent with the view that pigmentation of dark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 44 publications
8
60
1
Order By: Relevance
“…Several clues about the important role of Tyrp1 in Tyr function have also been provided by in vivo studies. Tyr catalytic function in the skin of brown mice is only 80% that found in the skin of black mice (36), and melanin content of brown mouse hair is only 30 -35% that found in black mouse hair (19,36).…”
Section: Tyrp1 Stabilization Of Tyrosinasementioning
confidence: 87%
“…Several clues about the important role of Tyrp1 in Tyr function have also been provided by in vivo studies. Tyr catalytic function in the skin of brown mice is only 80% that found in the skin of black mice (36), and melanin content of brown mouse hair is only 30 -35% that found in black mouse hair (19,36).…”
Section: Tyrp1 Stabilization Of Tyrosinasementioning
confidence: 87%
“…Previous studies carried out by us and others have shown that binding of the radiolabeled melanocortins NDP-MSH or ACTH to whole cells can be inhibited by recombinant Agouti protein (Lu et al 1994;Blanchard et al 1995;Siegrist et al 1997;Yang et al 1997 Geschwind (1966), Kobayashi et al (1995), Movaghar (1989), and Prota et al (1995), and as modified from Barsh (1996). During the switch from eumelanin to pheomelanin production caused by increased Agouti expression, tyrosinase activity is gradually downregulated.…”
Section: The Mc1r Is An Agouti Receptormentioning
confidence: 96%
“…Current data suggest that Bloc1 is involved in the sorting and budding of Tyr-and Tyrp1-containing vesicles from the trans-Golgi network, while Bloc2 may be involved in targeting or mediating fusion between small vesicles containing Tyr and/or Tyrp1 in the forming melanosome ( Figure 7D) (Wei 2006;Di Pietro et al 2006;Helip-Wooley et al 2007;Setty et al 2007;Huizing et al 2008;Sitaram and Marks 2012). Interestingly, eumelanin production requires Tyr, Tyrp1, and Tyrp2, while pheomelanogenesis requires only Tyr (Prota et al 1995). Although untested, our data are consistent with the hypothesis that, in the snw/hps5 I76N mutant, reduced Bloc2-dependent transport of Tyrp1 inhibits eumelanosome biogenesis ( Figure 7D).…”
Section: Hps5/hps6 Interaction Is Destabilized By I76nmentioning
confidence: 99%